A Rubik’s Cube®, the Copenhagen School and Israel A Re-conceptualisation of Security 1947–1967 - Felton, Tara (Curtin University, 2020)
What are you afraid of, and what will you do to protect yourself from that threat ? When envisioning the creation of a new state this dissertation lays the groundwork, for the incorporation of a multidimensional pre-state securitization structure which considers threats, opportunities and their flow-on effects. This methodology, as examined through the State of Israel is applicable to new states, and to better understand the success or failure of nation-states.